О прогнозировании характера анизотропии трещиностойкости стареющих металлических материалов - Каминский, А.А.; Нижник, С.Б. (Видавничий дім "Академперіодика" НАН України, 2008)
An approach is developed and experimentally validated to estimate and to predict an anisotropy of the crack-resistance characteristic K1C of plastically anisotropic ageing alloys acted by processes of technological deformation (rolling) and strengthening heat treatment. The crack-resistance anisotropy is studied with allowance for the influence of the anisotropy indices of structural parameters of the material on the planes of the growth of a mode I crack under loading in the directions of rolling, transverse, and normal to the rolling plane.